Determination of the size and forms of dust particles of some dust storms that were exposed to Salah al-Din Governorate - Iraq by FESEM (The Peerian Journal, 2024)
Preserving the environment and vital systems is necessary from this section This study came to highlight the levels of dust falling over Salah Al-Din Governorate during 2022-2023, as (6) samples were collected from the dust storms that the study area was exposed to, and these samples were prepared and prepared for measurement by scanning electron microscopy, and dust particles appeared in different shapes between the sharp pointed cylindrical shape and the rectangular shape with sharp heads and between the circular shape as well as salt shapes. Dust particles are characterized by being very small, as their sizes ranged as follows: A (48.67-56.57), B (44.70-52.03), C (44.80-62.36), D (51.69-64.46), E (48.67-56.37), F (44.80-62.36) nm. Therefore, these molecules have mechanical effects on the natural barrier of the human respiratory system, as well as injury to the eyes, skin and ear with diseases that are several of these results were within the permissible limits according to the World Health Organization, but you should avoid leaving the house at the time of the dust storm, not at the time of necessity due to health risks to the respiratory system